CURRENT TRENDS IN ACCOUNTING THEORY. - Hylton, Delmer P. (The Accounting Review, 1962)
Abstract This article focuses on the current trends in accounting theory. Two such movements seem to be apparent at the present time. One of these is the trend toward a closer relationship between accounting income and economic income; the other, a trend toward less reliance upon income tax regulation in the formulation of accounting theory. These two items are listed as trends, not as accomplished facts. With this in mind, this article may briefly examine some evidence of the existence of the trends. One current trend is the resurgence of the balance sheet. Partly as a result of the rush to LIFO, the income statement has been given primary emphasis in most areas of accounting during the past twenty years. The assertion that the measurement of income is the important task of accounting, and the balance sheet is nothing more than a receptacle for carrying forward amounts to be shown on future income statements, has been heard from many quarters. On the other hand, those who are concerned about the effects of inflation on depreciation have objected that the balance sheet does not show the proper amount to be carried forward to future years. Both groups then, deplored the balance sheet, although for different reasons.